Study of Effect of Iron Contamination in Drinking Water of Manihari Block, Katihar District, Bihar (India) and its Effect on Tribal Population - Jha, Nityandand; Deo, A.K. (Asian Journal of Chemistry, 2010)
The study of physico-chemical characteristics of drinking water with reference to iron contamination of two Panchayats namely Mahishpur and Miyanpur of Manihari Block of Katihar District, Bihar was made in Nov.-Dec. 2000. The parameter studied was iron etc.